Pertimbangan Penuntut Umum Memilih Tempat Terjadinya Tindak Pidana Dalam Mendakwa Pelaku Yang Melakukan Tindak Pidana di Luar Daerah Hukumnya Pada Surat Dakwaan Register Perkara: Pdm-15/Ppjng/Eoh.2/03/2021 - Yunita Eka Putri; Ismansyah Ismansyah; Aria Zurnetti (LPPM Universitas Ekasakti Padang, 2023)
Public Prosecutor is a prosecutor at the Attorney General's Office of the Republic of Indonesia who is authorized by law to conduct prosecutions, which process includes the authority to compose indictments. In exercising this authority, Article 15 and Article 137 of the Criminal Procedural Code (KUHAP) provide limitations for Public Prosecutors to conduct prosecutions within their jurisdictions, however, in practice it is found that Public Prosecutors indict criminal offenders who committed crimes outside their given jurisdiction (extra-jurisdictional). To study this phenomenon and its legal consequences, this research examines the consideration of the Public Prosecutor at Padang Panjang District Prosecutor's Office who indicted the perpetrator of criminal offense outside its given jurisdiction, as found in indictment No. PDM-15/PPJNG/Eoh.2/03/2021 on behalf of the defendant Aziarlis Bin Ameh Pgl Ziar, by employing empirical legal research methods based on primary data obtained by interviewing related Judges, lawyer and Public Prosecutors and also based on secondary data obtained through literature studies of various regulations and references that are analyzed qualitatively. This study finds that despite the restrictions imposed by KUHAP, extra-jurisdictional indictment is made possible through several provision in legislation, including Article 2 paragraph (3) of Law Number 16 Year 2004 concerning the Attorney General’s Office of the Republic of Indonesia. This study also recommends that the Supreme Court should consistently apply Article 4 paragraph (1) of Law No. 49 year 2009 concerning the Second Amendment to Law No. 2 Year 1986 concerning General Courts, which is included as a consideration in Chief Justice Decree No. 200/KMA/SK/X/2018.